Nanoparticle Delivery of Transition-Metal Chelators to the Brain: Oxidative Stress will Never See it Coming! - J. Bonda, David; Liu, Gang; Men, Ping; Perry, George; A. Smith, Mark; Zhu, Xiongwei (CNS & Neurological Disorders - Drug Targets, 2012)
The pathological lesions typical of Alzheimer disease (AD) are sites of significant and abnormal metal accumulation. Metal chelation therapy, therefore, provides a very attractive therapeutic measure for the neuronal deterioration of AD, though its institution suffers fundamental deficiencies. Namely, chelating agents, which bind to and remove excess transition metals from the body, must penetrate the blood-brain barrier to instill any real effect on the oxidative damages caused by the presence of the metals in the brain. Despite many advances in chelation administration, however, this vital requirement remains therapeutically out of reach: the most effective chelators-i.e., those that have high affinity and specificity for transition metals like iron and copper-are bulky and hydrophilic, making it difficult to reach their physiological place of action. Moreover, small, lipophilic chelators, which can pass through the brain’s defensive wall, essentially suffer from their over-effectiveness. That is, they induce toxicity on proliferating cells by removing transition metals from vital RNA enzymes. Fortunately, research has provided a loophole. Nanoparticles, tiny, artificial or natural organic polymers, are capable of transporting metal chelating agents across the blood-brain barrier regardless of their size and hydrophilicity. The compounds can thereby sufficiently ameliorate the oxidative toxicity of excess metals in an AD brain without inducing any such toxicity themselves. We here discuss the current status of nanoparticle delivery systems as they relate to AD chelation therapy and elaborate on their mechanism of action. An exciting future for AD treatment lies ahead.
Keywords: BBB